Study on Quality of Water from Various Resources of Tidal Zonetaken on Dry Season at Muliasari Village Tanjung Lago District - Indah Hamida; Robiyanto Hendro Susanto; PoedjiLoekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Contamination by organic matters, nutrient, pathogenic bacteria, micro pollutant and detergent/surfactant caused quality decrease of water in tidal zone. This study was aimed to evaluate quality of various water resources and to elaborate correlation between tidal environment condition and water resources quality at Muliasari village district of Tanjung Lago. Water sample was taken by purposive sampling method. Analysis result using Storet method showed average value of several parameters at high tide are: temperature 31.37°C;TSS 74.28 mg/L;pH 3.38; salinity 1.82; DO 5.05 mg/L; BOD 32.51 mg/L; COD 98.5 mg/L; ammonia 0.29 mg/L; phosphate 0.1690 mg/L; Fe 0.272 mg/L and Coliform 0.31/100 mg/L. At low tide these parameters had values for temperature 27.13°C; TSS 67.14 mg/L; pH 3.38; salinity 1.7; DO 4.86 mg/L; BOD 14.13 mg/L; COD 43.71; ammonia 0.244 mg/L; phosphate 0.1695 mg/L; Fe 0.232 mg/L and Coliform 0.32/100 mg/L. According to Governor’s provision no.16/2005 on water quality standard, water from various resources of Muliasari village were moderately polluted. Domestic waste water management is needed at this area followed by training and enhance occupant’s awareness to maintain hygiene and environment quality. Monitoring effort is also necessary on water resources quality for at least once every 6 months. Key words: Water quality, tidal zone, domestic waste